3d finite element simulation of reinforced concrete column strengthened by partially confined carbon fibre reinforced polymer under concentric loading - Fariz Aswan Ahmad Zakwan; Ruqayyah Ismail; Hazrina Ahmad; Raizal Saifulnaz Muhammad Rashid (Acta Polytechnica CTU Proceedings, 2022)
In this paper, numerical simulation initiated to investigate the mechanical response of reinforced concrete (RC) column strengthened by partially confined carbon fiber reinforced polymer (CFRP). An experimental investigation of the circular hollow unconfined and confined RC column enhances with a partially CFRP sheet has been performed to investigate its behavior under concentric loading on top of the RC column. From the experimental data, the critical buckling failure of the RC column observed. Therefore, the prediction behavior of the RC column strengthened with partially confined CFRP under concentric loading was made with the application of the general-purpose of ABAQUS finite element simulation. From the outcome of the simulation results, the predicted buckling failure compared and validated against the experimental data. The predicted model discovered to agrees well with the experimental work output.